The HF-LF minilab for analysing dielectric and semiconductor matter with the tunnel diod and corbino-electrodes in resonator - Бондаренко, И. Н.; Николаенко, В. А. (My University, 2020)
Study the quantum-size structures of matter is important in order to coupling nanotechnologies and use of the nanomaterials. The high frequency (HF) resonant method in research of semiconductors and dielectrics at low temperature is sensitive and exact in row others. This is due to high quality of resonance at low signal-to-noise ratio and at small energy loss in tested matter. The concept of "giga - nano" takes a place here. The use of compact tunnel diodes as the generator and detector coupled with resonator considered in this work is attractive for low-temperature studies of nanostructures. The feature of work is also that the bottom of resonator is coaxial system of rings - Corbino geometry. The Corbino system serves, on the one hand, as analyzer of matter properties of at low frequencies (LF), on other one, serves as a modulator of HF field in resonator. Filling the vacuumed cavity by various gases additionally can serve by the specific theme of researches. So, proposed HF-LF mini-analyzer of matter for the low- temperature investigation. The main composition of device on resonator basis is given.
Keywords: nanomaterials; dielectrics and semiconductors; HF cavity; superfluid helium